2013
DOI: 10.1590/s1516-89132013000200001
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic fermentation by the wild yeasts under thermal, osmotic and ethanol stress

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…Remarkable decrease of glucose concentration from 172.00 g/L to 0.81 g/L indicated that the yeast cells were alive, consumed glucose as the main substrate and grew rapidly and subsequently increased the immobilized cell activity. Based on their observation to the viable cells, da Silva et al [46] found that yeast S. cerevisiae strain BB.09 showed resistance up to 8 % v/v ethanol concentration, which is equivalent to 63.12 g/L even when temperature was increased to 35 °C. However, the alginate matrix gave protection to the entrapped yeast cells against ethanol stress and subsequently increased the number of survival immobilized cells as compared to free cells as reported by Norton and D'Amore [47].…”
Section: Results and Discussion 31 Fermentation Using Immobilized Yeast 311 Effect Of Time On The Ethanol Productionmentioning
confidence: 99%
“…Remarkable decrease of glucose concentration from 172.00 g/L to 0.81 g/L indicated that the yeast cells were alive, consumed glucose as the main substrate and grew rapidly and subsequently increased the immobilized cell activity. Based on their observation to the viable cells, da Silva et al [46] found that yeast S. cerevisiae strain BB.09 showed resistance up to 8 % v/v ethanol concentration, which is equivalent to 63.12 g/L even when temperature was increased to 35 °C. However, the alginate matrix gave protection to the entrapped yeast cells against ethanol stress and subsequently increased the number of survival immobilized cells as compared to free cells as reported by Norton and D'Amore [47].…”
Section: Results and Discussion 31 Fermentation Using Immobilized Yeast 311 Effect Of Time On The Ethanol Productionmentioning
confidence: 99%
“…Lo anterior se relaciona con la falta de estudios sobre BA tradicionales ya que su elaboración y venta no requieren procesos de industrialización y comercialización que obliguen a cumplir con los requerimientos exigidos por la ley para este tipo de BA, es por esto que, de acuerdo a las normas de ICONTEC el ñeque podría ser considerado como una BA fraudulenta (Olarte et al, 2007). (NTC 410, 1999) Mínimo 38 Máximo 300 Máximo 1 -La contaminación con metanol se origina cuando se produce la fermentación de jugos azucarados utilizados para la obtención de BA, en la cual, además de etanol, se producen también cantidades variables de metanol y demás compuestos volátiles (Olarte et al, 2007;López-Naranjo et al, 2013;Silva et al, 2013). Como se evidencia en la Tabla 1 los valores de metanol en ñeque de los corregimientos y municipios del Departamento de Bolívar no sobrepasan los límites permisibles nacionales (máximo 300 mg/L según NTC 410) ni internacionales (máximo 500mg/L) (Ministerio de Salud, 2001).…”
Section: Análisis De Resultadosunclassified
“…Ethanol inhibits cell growth, viability, and fermentation rate in yeast (Pratt et al, 2003). Yeast ethanol tolerance can be assessed by exposing the yeast culture to ethanol at different concentrations until cellular growth suppression occurs, an important tool to characterize yeast species and strains considered for application in alcoholic fermentations (Da Silva et al, 2013). We observed that the growth of M. megachiliensis decreased with increasing ethanol concentration in the medium, which is similar to the pattern displayed by other wild yeast isolates characterized by (Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%